2011
DOI: 10.1101/gad.611011
|View full text |Cite
|
Sign up to set email alerts
|

Tight protein–DNA interactions favor gene silencing

Abstract: The heterochromatin-like structure formed by the yeast silent information regulator complex (SIR) represses transcription at the silent mating type loci and telomeres. Here, we report that tight protein-DNA complexes induce ectopic recruitment of the SIR complex, promoting gene silencing and changes in subnuclear localization when cis-acting elements are nearby. Importantly, lack of the replication fork-associated helicase Rrm3 enhances this induced gene repression. Additionally, Sir3 and Sir4 are enriched gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 36 publications
4
93
0
Order By: Relevance
“…One simple model posits that SWI/SNF is required for efficient replication through SIR heterochromatin and that HU-induced fork stress heightens the need for SWI/SNF to remove Sir3p. Alternatively, Taddei and colleagues have shown that Sir proteins can be recruited to stalled replication forks (34). Perhaps SWI/SNF plays a role in removing Sir proteins from stalled forks, alleviating the negative consequences of this Sir recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…One simple model posits that SWI/SNF is required for efficient replication through SIR heterochromatin and that HU-induced fork stress heightens the need for SWI/SNF to remove Sir3p. Alternatively, Taddei and colleagues have shown that Sir proteins can be recruited to stalled replication forks (34). Perhaps SWI/SNF plays a role in removing Sir proteins from stalled forks, alleviating the negative consequences of this Sir recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, tight protein-DNA interactions, like those formed by the Pol III machinery at tRNA genes, promote recruitment of Sir2/3/4 complexes to chromatin in certain contexts (Dubarry et al 2011). Typically, this activity is suppressed by the Rrm3 helicase that facilitates replication-fork passage through nonhistone DNA complexes.…”
Section: Potential Cell Cycle Regulators Of Silent Chromatin Establismentioning
confidence: 99%
“…This, in combination, with the expression of a green fluorescent protein (GFP)-LacI repressor allows for visualization of promoter location in the embryo and throughout larval stages in development. Importantly, for tracking genes with the LacO repeats inserted, small arrays are used so as to not introduce potential chromatin structure artifacts (e.g., the array acting as a silencer itself) (44), and results are further validated by fluorescence in situ hybridization (FISH). With the LacO system, both gut (pha-4)-and muscle (myo-3)-specific promoters are inactive and sequestered at the nuclear periphery throughout early development; however, the promoters are transcriptionally active and found in the nuclear interior in differentiated gut and muscle cells, respectively (45).…”
Section: Gene Positioning To the C Elegans Npcmentioning
confidence: 99%